Evaluation of Hole Quality on Microdrilling AISI304 Austenitic Stainless Steel - Widodo; Redzuan, N.; Kurniawan, Denni (2015)
© 2015 The Authors The main objective of this study is to investigate and optimize the hole roundness when drilling a micro hole diameter 0.80 mm on AISI 304 austenitic stainless steel using solid carbide micro drill. There are three machining parameter of this experiment which is spindle speed, feed rate and depth of cut. An experiment plan with 2 3 factorial design single replication plus three center point was executed. The hole roundness measurement were carried out using CMM Mitutoyo Beyond Crista C7106 that equipped with Renishaw PH10T with low force TP200 stylus module. The analysis of optimum parameter using design expert software and conclude that the most significant factor affected to the hole roundness is spindle speed and feed rate. The R 2 value 0.9964 is high and “Pred R-Squared” value 0.9821 also in reasonable agreement with the “Adj R-Squared” of 0.9920. The optimum result could be achieved when the spindle speed; feed rate and depth of cut at low level.